PERTUMBUHAN DAN HASIL TIGA VARIETAS JAGUNG MANIS (Zea mays saccharata Sturt) TERHADAP BERBAGAI DOSIS PUPUK ORGANIK HAYATI PADA LAHAN RAWA LEBAK - Khairiyah Khairiyah; Siti Khadijah; Muhammad Iqbal; Sariyu Erwan; Norlian Norlian; Mahdiannoor Mahdiannor (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2017)
In Indonesia, corn is an important food commodity after rice, so its production must be improved. That can be done to increase corn production is by using the right varieties and the provision of fertilizer, one of them by using biofertilizer. This study aims to (1) determine the effect of interaction between varieties with the dosage of biological fertilizer, (2) to know the effect of varieties, (3) to know the effect of the dosage of biological fertilizer, (4) get the best interaction between varieties with biofertilizer, (5) get the best varieties, (6) get the best biofertilizer dose on growth and sweet corn yield on swamp land. This research was conducted in Tambalang Kecil Village, Sungai Pandan from April to July 2017. Using Factor Random Design (RAK) Factorial 2 factors. The first factor is varieties with 3 levels: v1 = Janisa F1 Varieties, v2 = Bonanza F1 Varieties, v3 = Super Sweet Corn Varieties. The second factor is the dosage of Migro Green biological fertilizer with 3 levels: h1 = 4 ℓ.ha-1 equivalent to 1.38 mℓ.plot-1, h2 = 6 ℓ.ha-1 equivalent to 2.06 mℓ.plot-1, h3 = 8 ℓ.ha-1 is equivalent to 2.75 mℓ.plot-1. The results showed that the interaction between the varieties and the biological fertilizer did not affect the growth and results, but the significant effect on the weight of cob without cornhosk, while the single factor varieties significantly affect the growth and very significant effect on yield components and biofertilizer has no effect on the vegetative growth component, but have a significant effect on generative growth component and yield component.